Demethylzeylasteral suppresses the expression of MESP1 by reducing H3K18la level to inhibit the malignant behaviors of pancreatic cancer - Xiaolei Ma; Mengxing Cheng; Yanxin Jia; Kun Zhang; Haocheng Zhang; Di Feng; Wenxiao Xu; Guofen Qiao (Cell Death Discovery)
Abstract Glycolysis is a hallmark metabolic pathway in pancreatic cancer (PC). As the end product of glycolysis, lactic acid accumulates significantly in PC. Lactic acid serves as a primary substrate for histone lactylation, leading to an upregulation of histone lactylation levels, which likely contributes to progression of PC. This study reveals novel insights, highlighting that H3K18la levels are elevated in PC tissues and cells. Notably, the natural compound demethylzeylasteral (DML), derived from Tripterygium wilfordii Hook F (TwHF), substantially decreases lactic acid generation in PC cells, subsequently resulting in the downregulation of H3K18la levels and inhibiting the aggressive characteristics of PC cells. To further investigate the underlying mechanisms, we conducted RNA-seq analysis on DML-treated cells and ChIP-seq analyses for H3K18la. For the first time, mesoderm-related factor 1 (MESP1) was identified as a target protein modulated by both DML and H3K18la. DML was shown to repress the expression of MESP1, while sodium lactate (Nala) was found to partially restore its expression levels. Overexpression of MESP1 was linked to the promotion of epithelial-mesenchymal transition (EMT) and apoptosis in PC cells. Furthermore, RNA-seq analyses following MESP1 silencing indicated its significant association with critical physiological processes in PC cells, including the cell cycle, apoptosis, and cell adhesion. Importantly, MESP1 has also been connected to various cancer metabolism pathways, such as MAPK, PI3K-AKT, and carbon metabolism. This research is groundbreaking in demonstrating that DML impedes the malignant behavior of PC cells by downregulating H3K18la levels and diminishing the expression of the oncogene MESP1.